Congenic strains reveal the effect of the renin gene on skeletal muscle angiogenesis induced by electrical stimulation - de Resende, Micheline M.; Amaral, Sandra L. [UNESP]; Moreno, Carol; Greene, Andrew S. (Amer Physiological Soc, 2008)
Previous studies have indicated the importance of angiotensin II (ANG II) in skeletal muscle angiogenesis. The present study explored the effect of regulation of the renin gene on angiogenesis induced by electrical stimulation with the use of physiological, pharmacological, and genetic manipulations of the renin-angiotensin system (RAS). Transfer of the entire chromosome 13, containing the physiologically regulated renin gene, from the normotensive inbred Brown Norway (BN) rat into the background of an inbred substrain of the Dahl salt-sensitive (SS/Mcwi) rat restored renin levels and the angiogenic response after electrical stimulation. This restored response was significantly attenuated when SS-13BN/Mcwi consomic rats were treated with lisinopril or high-salt diet. The role of ANG II on this effect was confirmed by the complete restoration of skeletal muscle angiogenesis in SS/Mcwi rats infused with subpressor doses of ANG II. Congenic strains derived from the SS-13BN/Mcwi consomic were used to further verify the role of the renin gene in this response. Microvessel density was markedly increased after stimulation in congenic strains that contained the renin gene from the BN rat (congenic lines A and D). This angiogenic response was suppressed in control strains that carried regions of the BN genome just above (congenic line C) or just below (congenic line B) the renin gene. The present study emphasizes the importance of maintaining normal renin regulation as well as ANG II levels during the angiogenesis process with a combination of physiological, genetic, and pharmacological manipulation of the RAS.
Keywords: renin-angiotensin system; chromosomal substitution